Role-reversal and discussion-oriented models for flipping digital vocabulary achievement in English classrooms for Electronic Engineering learners - Sutrisno, Djoko; Annury , Muhammad Nafi (Teaching English as a Foreign Language Journal, 2022)
This research aims to verify whether two classroom models, discussion-oriented and role-reversal, have an effective strategy for teaching vocabulary achievement to English language learners. The proposed models were examined as a successful method for teaching and learning vocabulary. A quasi-experimental strategy was used with three intact classes: one control (Electronic Engineering Learners A class) and two experimental (B and C class) (Electronic Engineering Learners B and C class). Using pre- and post-test writings, the effectiveness of the two models, which incorporated two digital applications, was determined. Additionally, a questionnaire created by the researcher and a semi- structured interview was used to assess vocabulary achievement. Covariance analysis revealed that classrooms that emphasized discussion and role reversal were more effective than those that did not. In terms of vocabulary growth in post-test expository writing, the role-reversal group also outperformed the discussion-oriented group. Further analyses revealed the positive perceptions and experiences surrounding flipped classrooms, highlighting four themes: instructor support, personal sentiment, peer support, and activities beyond the classroom. This report concludes by emphasizing the need for further research into this potential technology-based pedagogy across diverse language skills and the incorporation of technology in Vocabulary Achievement.